Alleged Violation of Article 22 of Law Number 5 of 1999 Regarding the Procurement of Road Construction Work Packages (Acceleration Program) Package 3 (Pelangan-Sp. Pengantap 3) and Package 4 (Pelangan-Sp. Pengantap 4) at the Public Works and Spatial Planning Service Working Unit West Nusa Tenggara Province APBD Fiscal Year 2017-2018 Decision: 35/KPPU-I/2020 - Manurung, Agustinus; Faisal, Ryan; Cahyad, Aep Hendar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes alleged violations of Article 22 of Law no. 5 of 1999 regarding the practice of rigging tenders in the procurement of Packages 3 and 4 for road construction in NTB in 2017-2018. The analysis was carried out based on KPPU decision Number 35/KPPU-I/2020 and various other sources of information. The results of the analysis show that there are strong indications of violations of Article 22 of Law no. 5 of 1999, with horizontal and vertical conspiracy modes